Impact of a two-dose varicella immunization program on the incidence of varicella: a multi-year observational study in Shanghai, China. (2nd September 2021) - Li, Zhi; Yao, Ye; Lu, Xinyue; Liu, Jiechen; Huang, Zhuoying; Sun, Xiaodong; Lu, Yihan
ABSTRACT: Background: It remains hesitant to include a two-dose varicella vaccine (VarV) in a national routine immunization program in China. We aimed to quantify the impact of the two-dose VarV on varicella incidence in Shanghai. Research design and methods: We directly extracted the data of varicella cases and VarV doses in 2013–2020 in Shanghai, and then estimated the effects of two-dose VarV using a Serfling model. Results: A two-dose VarV immunization program has been extensively implemented since October 2017 and become free since August 2018 in Shanghai. Before and after this program, varicella cases significantly declined in children (P < 0.01), whereas did not in adults aged >18 years (P = 0.22). Compared to the predicted number of varicella cases, actual number was significantly lower by 8% in 2018 and 28% in 2019. Among children aged 4–6 years, the reduction in varicella cases was largest. Moreover, there was a significant reduction in varicella cases throughout 2020 (P < 0.001), in which the decrease due to social distancing for the COVID-19 was 54%. Conclusions: A two-dose VarV immunization program may further reduce approximately one-third of varicella cases in Shanghai. Children <4 years and adults benefit less in this program, which warrants enhancing the immunization.